Design, synthesis and biological evaluation of 2-((4-sulfamoylphenyl)amino)-pyrrolo[2, 3-d]pyrimidine derivatives as CDK inhibitors. (31st December 2023) - Yang, Bo; Quan, Yanni; Zhao, Wuli; Ji, Yingjie; Yang, Xiaotang; Li, Jianrui; Li, Yi; Liu, Xiujun; Wang, Ying; Li, Yanping
Abstract: To explore the potential use of CDK inhibitors in pancreatic ductal adenocarcinoma (PDAC) therapy, a series of novel 2-((4-sulfamoylphenyl)amino)-pyrrolo[2, 3-d]pyrimidine derivatives was designed, synthesised, and investigated for inhibition on both CDK kinase activity and cellular proliferation of pancreatic cancer. Most of new sulphonamide-containing derivatives demonstrated strong inhibitory activity on CDK9 and obvious anti-proliferative activity in cell culture. Moreover, two new compounds suppressed cell proliferation of multiple human pancreatic cancer cell lines. The most potent compound 2g inhibited cancer cell proliferation by blocking Rb phosphorylation and induced apoptosis via downregulation of CDK9 downstream proteins Mcl-1 and c-Myc in MIA PaCa-2 cells. CDK9 knockdown experiment suggests its anti-proliferative activity is mainly mediated by CDK9. Additionally, 2g displayed moderate tumour inhibition effect in AsPC-1 derived xenograft mice model. Altogether, this study provided a new start for further optimisation to develop potential CDK inhibitor candidates for PDAC treatment by alone or combination use.